2009
DOI: 10.1007/s10592-008-9799-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 12 microsatellite loci for Michelia coriacea (Magnoliaceae), a critically endangered endemic to Southeast Yunnan, China

Abstract: By using a modified biotin-streptavidin capture method, a total of 12 microsatellite loci were developed and characterized for Michelia coriacea (Magnoliaceae), a critically endangered endemic to Southeast Yunnan, China. The number of alleles (A) ranged from two to six in 30 samples of this species. The ranges of observed (H O ) and expected (H E ) heterozygosities were 0.033-0.8000 and 0.033-0.7910, respectively. Cross-species amplification in M. yunnanensis showed that a subset of these markers holds promise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Similar to other endangered Magnoliaceae species (Zhao et al, 2009; Sun et al, 2010), substantial genetic diversity was found in the investigated populations of T. odorum . The battery of microsatellite markers presented here provides a powerful tool for further investigation of the genetic structure, mating system, and gene flow of T. odorum , which are highly valuable for formulating conservation strategies.…”
Section: Discussionsupporting
confidence: 75%
“…Similar to other endangered Magnoliaceae species (Zhao et al, 2009; Sun et al, 2010), substantial genetic diversity was found in the investigated populations of T. odorum . The battery of microsatellite markers presented here provides a powerful tool for further investigation of the genetic structure, mating system, and gene flow of T. odorum , which are highly valuable for formulating conservation strategies.…”
Section: Discussionsupporting
confidence: 75%
“…Michelia coriacea is diploid (2 n = 38) [ 39 ]. The mature trees can reach up to 20–30 m in height and 50–60 cm in diameter [ 18 , 19 , 40 ], and live for at least 100 years. The species bears scented whitish or creamy yellow flowers with 6–7 tepals which are in anthesis from February to April [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…SSR genotyping was performed according to the methods described in Zhao et al [ 40 ] at loci MC2, MC3, MC8, MC34, MC35, MC41, MC45, MC48, MC49, MC64, and MC66 ( Table 2 ). Briefly, SSR loci were amplified by PCR in a final volume of 15 μL containing 7.5 μL 2× Taq PCR MasterMix (Tiangen; 0.1 U Taq Polymerase/μL, 0.5 mM dNTP each, 20 mM Tris-HCl, 100 mM KCl, 3 mM MgCl 2 ), 20–50 ng genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Extracted DNA was dissolved in 50 μL Tris-EDTA (TE) buffer and stored at −20°C for amplification via polymerase chain reaction (PCR). Through preliminary screening using plastid and nuclear primers, 3 universal cpDNA intergenic spacers (matK, psbA-trnH, and TrnL-trnF) and 10 microsatellite markers were selected from 32 recently developed nuclear microsatellites in Magnoliaceae (Zhao et al, 2009 ; Sun et al, 2010 ; Li et al, 2012 ) on the basis of their clarity and reproducibility.…”
Section: Methodsmentioning
confidence: 99%